Réponses

  • Utilisateur Brainly
2014-04-06T17:05:37+02:00
Soit B= (3x+4)²-81

a- Développe l'expression B
B=(3x+4)²-81
B=9x²+24x+16-81
B=9x²+24x-65

b- Factorise B
B=(3x+4)²-9²
B=(3x+4-9)(3x+4+9)
B=(3x-5)(3x+13)

c- Calcule B pour x = -5 puis pour x = 5 sur 3
B(-5)=9*25-25*5-65=40
B(5/3)=0

d- Résous l'équation B = 0

(3x-5)(3x+13)=0
3x-5=0 ou 3x+13=0
x=5/3 ou x=-13/3
2014-04-06T17:06:00+02:00
Bonjour

Soit B= (3x+4)²-81

 a- Développe l'expression : B = 9x² + 24x + 16 -81 = 9x² +24x - 65

 B b- Factorise B : B = (3x+4 -9)(3x+4 +9) = (3x -5)(3x +13)

c- Calcule B pour x = -5 : B = (-15-5)( - 15 +13) = -20 x - 12 = 240

puis pour x = 5 sur 3 B = ((15/3 -5)(15/3 +13) = (15/3 - 15/3)( 15/3 + 39/3) = 0

 d- Résous l'équation B = 0

(3x-5)(3x+13) = 0
soit 3x +5 = 0 donc 3x = -5 et x = -5/3
soit 3x +13 = 0 donc 3x = -13 et x = -13/3